IRETA: a window on the South Pacific - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Towards the end of 1980, the Heads of Agriculture of the South Pacific Islands agreed to support the University of the South Pacific (USP) in establishing an Institute for Research, Extension and Training in Agriculture (IRETA), using the resources...